2016
DOI: 10.1155/2016/4386836
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Fault Slip Induced by Stress Waves

Abstract: Fault slip burst is a serious dynamic hazard in coal mining. A static and dynamic analysis for fault slip was performed to assess the risk of rock burst. A numerical model FLAC3D was established to understand the stress state and mechanical responses of fault rock system. The results obtained from the analysis show that the dynamic behavior of fault slip induced by stress waves is significantly affected by mining depth, as well as dynamic disturbance intensity and the distance between the stope and the fault. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…For the overlying strata of 21304 panel, the sudden caving of the siltstone layer (11 m thick and 23.14 m above the entry) will generate a dynamic load on the entry. Previous studies [34] have shown that, if the dynamic disturbance source is induced by roof caving, the waveform usually belongs to the single-peak waveform. erefore, the P-wave can be used in the simulation of the dynamic load.…”
Section: Dynamic Modelingmentioning
confidence: 99%
“…For the overlying strata of 21304 panel, the sudden caving of the siltstone layer (11 m thick and 23.14 m above the entry) will generate a dynamic load on the entry. Previous studies [34] have shown that, if the dynamic disturbance source is induced by roof caving, the waveform usually belongs to the single-peak waveform. erefore, the P-wave can be used in the simulation of the dynamic load.…”
Section: Dynamic Modelingmentioning
confidence: 99%
“…timing for reactivation of the faults [28][29][30][31]. During the propagation of a dynamic/blast wave, part of the stress wave energy will be absorbed by the preexisting faults, resulting in an increase of energy before it arrives at the faults and the attenuation of energy after crossing the faults [32][33][34]. e stress wave probably originates from ruptures of rock and coal masses, breakage, and/or collapse of the roof or blast loading in the stope.…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…e stress wave probably originates from ruptures of rock and coal masses, breakage, and/or collapse of the roof or blast loading in the stope. e energy disturbance along and through the preexisting faults has a large influence on the evolution and distribution of dynamic disasters such as rockbursts and the sudden reactivation of faults in coal mining [33].…”
Section: Shock and Vibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, dynamic rupture events in recent past had posed severe threats to mine workers thus adversely affecting continuous production in coal mines [1]. In recent years, many scholars have studied dynamic rupture induced by hard rock [14], coal pillar [15,16], fault [17,18] and tectonic stress [19,20], employing stress, strain and energy, and so forth as frequently used parameters but very few literatures had focused on floor dynamic rupture. This paper investigates mechanical mechanism of floor dynamic rupture by adopting an elastic thin plate theory.…”
Section: Introductionmentioning
confidence: 99%